The diet of post-breeding Antarctic shags Phalacrocorax bransfieldensis at the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge; Baroni, A.; Ramón, A.; Bertolin, María Lila; Di Prinzio, Cecilia Yanina (Antarctic Science)
The diet of post-breeding Antarctic shags Phalacrocorax bransfieldensis was investigated at four colonies at the Danco Coast, Antarctic Peninsula, by the analysis of 399 pellets (regurgitated casts) collected during February and March 1998 and 2000. Overall, demersal-benthic fish were the most frequent and important prey at all the colonies sampled, followed by octopods and gastropods. Amongst the fish, Notothenia coriiceps and Gobionotothen gibberifrons were the main prey in all of the sampling sites in both seasons. The composition of the diet of post-breeding shags differed from that observed in the previous breeding season. Post-breeders preyed on the same fish species consumed by breeders, although in different proportions and on larger specimens. The information provided here differs from that reported for post-breeding individuals belonging to other shag species and also for post-breeding Antarctic shags. Our results, as well as the differences with previous studies, are discussed in relation to differences in prey availability among localities and to the use of alternative foraging grounds at the end of the breeding period. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Baroni, A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Ramón, A. Municipalidad de Esquel. Subsecretaría de Medioambiente; Argentina Fil: Bertolin, María Lila. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Di Prinzio, Cecilia Yanina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina